Hukum Attakhattî (Melangkahi Pundak Jamaah) Ketika Khutbah Hari Jum’at Menurut Perspektif Mazhab Hanafi Dan Mazhab Syafi’i - Ismail, Ismail; Sa'adah, Sa'adah; Muttaqin, Zainal (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract Friday is a special day for Muslims, explained by Ibn Kathir as a day of gathering. On this day, the Friday prayer (Salat al-Jumu'ah) is performed, consisting of two obligatory units (rak'ahs) following two sermons (khutbahs), with specific conditions and pillars that must be met for the prayer to be valid according to Islamic law. One important aspect discussed in the context of Friday prayer is the prohibition of "attakhatti," which refers to stepping over the shoulders of worshipers during the sermon. This act is viewed differently by the Hanafi and Shafi'i schools of thought. The Hanafi school considers the act to be forbidden (haram) as it occurs during the sermon and has the potential to disturb other worshipers. In contrast, the Shafi'i school views attakhatti as merely disliked (makruh), though both agree that it disrupts the congregation. This study uses a normative legal research method with a descriptive and comparative approach, analyzing Islamic law books and fiqh texts from various schools of thought. The results reveal that the difference of opinion between the Hanafi and Shafi'i schools regarding attakhatti stems from divergent interpretations of the evidence (dalil). This highlights the variations in Islamic legal interpretation, particularly concerning actions that disrupt the performance of the Friday prayer. Keywords: Friday prayer, khutbah, attakhatti, Hanafi school, Shafi'i school, Islamic law Abstrak Hari Jum'at merupakan hari istimewa bagi umat Islam, yang dijelaskan oleh Ibnu Katsir sebagai hari berkumpul. Pada hari ini dilaksanakan ibadah salat Jumat, yaitu salat wajib dua rakaat yang dilaksanakan setelah dua khutbah, dengan syarat dan rukun yang harus dipenuhi agar sah menurut syariat Islam. Salah satu aspek penting yang dibahas dalam konteks salat Jumat adalah larangan melakukan perbuatan "attakhatti" atau melangkahi pundak jamaah saat khutbah. Perbuatan ini memiliki pandangan berbeda dalam mazhab Hanafi dan Syafi'i. Mazhab Hanafi menganggap perbuatan tersebut haram, karena dilakukan saat khutbah berlangsung dan berpotensi mengganggu jamaah lain. Sementara itu, mazhab Syafi'i memandang attakhatti sebagai makruh, meskipun keduanya sependapat bahwa perbuatan ini bisa mengganggu jamaah. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan deskriptif dan komparatif, mengkaji buku-buku hukum Islam dan kitab-kitab fiqih dari berbagai mazhab sebagai bahan analisis. Dari hasil penelitian, perbedaan pendapat antara mazhab Hanafi dan Syafi'i terkait attakhatti disebabkan oleh perbedaan dalam memahami dalil-dalil yang digunakan oleh masing-masing mazhab. Hal ini menunjukkan adanya variasi dalam interpretasi hukum Islam, khususnya terkait tindakan yang dianggap mengganggu pelaksanaan ibadah salat Jumat. Kata kunci: Salat Jumat, khutbah, attakhatti, mazhab Hanafi, mazhab Syafi'i, hukum Islam